Diabetes - Goodheart, Barbara (New York : F. Watts, 1990)
Looks at the condition of diabetes, what is necessary for a diabetic to maintain proper health, what must be done in the event of an insulin reaction, and the possibilities of a cure.
Includes bibliographical references (p. 119-120) and index.
Booklist.
Wilson's Senior High School.
7.4
7.4
7-10.
Keywords: Diabetes -- Juvenile literature; Diabetes; Diabetes